'GutFeel': an in silico method for predicting gut health status based on the metabolic functional capabilities of the resident microbiome. Issue 13 (3rd June 2021) - Anand, Swadha; Bose, Chandrani; Kaur, Harrisham; Mande, Sharmila S.
Abstract : Dysbiosis or imbalance in the gut microbiome has been correlated with the etiology of a number of diseases/disorders. Thus, gut microbial communities can potentially be utilized for assessing the health of the human gut. Although the taxonomic composition of the microbiomes is dependent on factors such as diet, lifestyle, and geography, these microbes perform a specific set of common functions in the gut. In this study, metabolic pathway‐based markers (agnostic to above‐mentioned factors) specific to commensals and those specific to pathogens are utilized as indicators of gut health. Furthermore, this gut health assessment requires only a small set of features rather than complete sequencing of metagenomes. The proposed scheme can also be used to design personalized biotherapeutics, depending on functional aspects observed in an individual. Abstract :